Case Report: Hyper IgM Syndrome Identified by Whole Genome Sequencing in a Young Syrian Man Presenting With Atypical, Severe and Recurrent Mucosal Leishmaniasis - Drabe, Camilla Heldbjerg; Marvig, Rasmus L.; Borgwardt, Line; Lundgren, Jens D.; Maquart, Hanne Vibeke Hansen; Katzenstein, Terese Lea; Helleberg, Marie (Frontiers in Immunology, 2020)
A previously healthy 19-year-old Syrian man presented with atypical and severe mucosal leishmaniasis caused by Leishmania tropica. During a 2-year period, he had three severe relapses despite various treatment strategies, including liposomal amphotericin B and Miltefosine. Because of the unusual clinical presentation, potential underlying immunodeficiency was investigated. Normal T and NK cell counts were found. The B cell count was slightly elevated at 0.7 x 109 cells/L (0.09–0.57 x 109 cells/L), but the proportions of memory and isotype switched memory B cells were severely diminished IgG levels were low, at 309 mg/dL (610–1490 mg/dL). The initial IgM and IgA levels were within normal range, but the IgA levels decreased to 57 mg/dL (70–430 mg/dL) during follow up. Common variable immunodeficiency (CVID) was initially suspected, because the immunological results of low IgG and IgA, low switched memory B cells, no profound T cell deficiency found and absence of secondary cause of hypogammaglobulinemia were compatible with this diagnosis (ESID 2019). However, the highly unusual and severe clinical presentation of L. tropica is not suggestive of B-cell deficiency or CVID. Eventually a pathogenic nonsense variant in the CD40 ligand gene (p.(Arg11*)) was identified by whole genome sequencing, thus enabling the diagnosis of X-linked hyper IgM syndrome. This case illustrates and supports the potential for the use of whole genome sequencing in accurate diagnosis of primary immunodeficiencies.